A History of Christianity in Asia, Africa, and Latin America, 1450-1990: A Documentary Sourcebook - Koschorke, Klaus (Wm. B. Eerdmans Publishing Co., 2007)
Intro -- Title Page -- Copyright -- Contents -- Preface -- Standard Works and Literature Quoted in Abbreviations -- Abbreviations and Omissions -- Asia -- I. Asia 1450-1600 -- A. Christians in Asia before the Arrival of the Portuguese -- 1. St. Thomas Christians in India -- a. Testimony of the Italian traveler Nicolò Conti (1415-1439) -- b. A Syrian Document from c. 1504 -- 2. Nestorians and Armenian Christians in Southern Asia (1508) -- 3. Jews and Christians in China -- a. Jews in Kaifeng: The Stele of 1489 -- b. Matteo Ricci on the Jews of Kaifeng (1605) -- c. Matteo Ricci on the Remnants of Chinese Christianity (1605) -- B. Early Portuguese Contacts -- 4. Searching for "Christians and Spices" (1498) -- 5. Fictitious and Actual Contacts with the St. Thomas Christians -- a. Visiting a "Church" in Calicut (1498) -- b. Failure with the Samorin in Calicut (1498) -- c. The Mission of Cabral (1500) -- 6. The Arrival of the Portuguese from an Arab Perspective -- 7. St. Thomas Christians on the Arrival of the Portuguese (1504) -- C. The Organization of Colonial Churches -- 8. Portuguese and Spanish Patronage in Mission -- a. The Papal Bull "Inter cetera" from Pope Calixtus III (1456) -- b. The Exercise of Patronage in the Philippines (1580) -- 9. Goa as a Political and Ecclesiastical Center -- a. The Raising of Goa to the Seat of the Bishopric (1534) -- b. Complaints about the Immorality of Settlers and Clergy -- c. Position of the Non-Christians (1522) -- d. The Introduction of the Inquisition in Goa (1543) -- D. Francis Xavier in Asia (1542-1552) -- 10. India -- a. Goa (1452) -- b. South India: The Paravas (1542-1544) -- 11. Southeast Asia: The Sultanate of Ternate -- 12. Japan -- a. First Plans -- b. Experiences in Japan -- 13. Plans for China -- E. Intercultural Contacts.